Two New Species of Xenotarsonemus (Acari: Tarsonemidae) from the Atlantic Forest, Brazil - Lofego, A. C. [UNESP]; Cavalcante, A. C.C.; Demite, P. R. (Springer Nature, 2018)
Two new species, Xenotarsonemus quiriri n. sp. and Xenotarsonemus scorpius n. sp., are described and illustrated in this paper based on specimens collected on Myrtaceae plants in Atlantic Forest areas of the states of Bahia and Santa Catarina, Brazil. A key to identification of Xenotarsonemus species reported from Brazil is provided.
Keywords: Diversity; hotspot; Myrtaceae; taxonomy